2005
DOI: 10.1021/cm048367g
|View full text |Cite
|
Sign up to set email alerts
|

Organic−Inorganic Hybrid Zeolites with Framework Organic Groups

Abstract: A novel type of organic−inorganic hybrid zeolite has been successfully synthesized, in which lattice oxygen atoms are partially superseded by methylene groups. Various types of hybrid materials with the LTA, MFI, and *BEA structures are obtained from an organosilane in which a methylene group bridges two silicon atoms under synthesis conditions similar to those for conventional zeolites. The presence of a methylene group in the framework is demonstrated by 29Si and 13C MAS NMR and IR, although the Si−C bonds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 39 publications
1
65
0
Order By: Relevance
“…Recently, Yamamoto et al [5,6] have prepared successfully a new family of microporous molecular sieves (MMS) called ZOL. ZOL refers to zeolites with organic groups bridged lattices and are defined as a true hybrid organic-inorganic material, where true means that the organic moieties, i.e., methylene groups (CH 2 ) are incorporated in the framework of the zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yamamoto et al [5,6] have prepared successfully a new family of microporous molecular sieves (MMS) called ZOL. ZOL refers to zeolites with organic groups bridged lattices and are defined as a true hybrid organic-inorganic material, where true means that the organic moieties, i.e., methylene groups (CH 2 ) are incorporated in the framework of the zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…[5] A more successful approach for synthesizing hybrid zeolites involves using bis-silylated organic precursors of general formula (R'O) 3 SiÀRÀSi(OR') 3 (R = CH 2 , CH 2 CH 2 ; R' = CH 3 , CH 2 CH 3 ) as silica source. [6][7][8] However, the much lower than expected organic content indicates that the Si À C bonds undergo hydrolysis. In any case, incorporation of methylene groups within the zeolite framework (an isomorphous substitution of ÀOÀ by ÀCH 2 À) is still debated because of the impossibility to distinguish a methylene group in the framework from one in the amorphous impurities that are usually present.…”
mentioning
confidence: 98%
“…The organomodified LTA zeolite showed larger n-hexane adsorption capacity than regular LTA zeolite. The same authors reported the preparation of other organo-modified zeolitic materials, ZOL family [86,87]. Díaz et al [88] and Su et al [89] have described the synthesis and characterization of new hybrid organozeolites containing high organic content following a similar synthesis methodology to Yamamoto.…”
Section: Direct Synthesis Of Hybrid Organic-inorganic Zeolitesmentioning
confidence: 99%